Bandwidth allocation for wired and wireless connections - Rajani, Balakrishnan (2008)
This project is a systematic study of "Bandwidth Allocation" in networks. IT comprises of two main strategies of networking namely wired networks and wireless networks. The problem of bandwidth allocation has been extensively studied for wired and wireless domain. But very little attention has been paid for wired-cum-wireless network topologies. This paper focuses on issues that make a wireless scenario different from a wired one. In the project the various algorithm that are used in wireless networks have been discussed and simulation approaclles have been done to simulate a communications throughput. Examples of graphical results have been illustrated and compared. A comparison of the important features of wired and wireless networks have been tabulated. The technique of bandwidth allocation is an ever evolving problem, thus many attempts have been made to make bandwidth allocation fair and justifiable. This study will give a good idea about these attempts as well as highlight the issues involved. (Author's abstract)